Consumer electronics : advanced - 3G Elearning FZ LLC (United Arab Emirates : 3G Elearning FZ LLC, 2016)
Consumer Electronics: Advanced comprehends various diverse practical and visual skills with knowledge of specialized materials and techniques. Consumer electronics are electronic equipment intended for everyday use, most often in entertainment, communications and office productivity. This book will introduce the knowledge and skills for those studying and/or working in construction sector to interpret and convey information in response to workplace requirements.
Includes index.
In English text.
Keywords: Household electronics; Electronic apparatus and appliances